Uji Aktivitas Antioksidan Ekstrak Metanol Bunga dan Daun Patikala (Etlingera elatior (Jack) R.M.Sm) Menggunakan Metode DPPH - Virsa Handayani; Aktsar Roskiana Ahmad; Miswati Sudir (Universitas Indonesia, 2014)
Patikala (Etlingera elatior (Jack) R.M.Sm) is a plant of the Zingiberaceae family. Bioactive compounds of patikala (Etlingera elatior (Jack) R.M.Sm) are flavonoids that act as antioxidants. The purpose of this study was to measure free radical activity in the methanol extract of the flowers and leaves of patikala (Etlingera elatior (Jack) R.M.Sm). Extraction of flowers and leaves samples was conducted with maceration method using methanol. Chemical compounds was qualitatively analyzed with specific eluent using Thin Layer Chromatography (TLC) to determine the group of active compounds in the extract. Antioxidant activity assay used the immersion method of DPPH (1,1-Diphenyl-2-picryl Hidrazil) to measure the absorption at the wavelength of 517 nm and to be compared with the antioxidant activity of quersetin. The results showed that the methanol extract rendemen was at 1.935% for flowers and at 5.17% for leaves. Antioxidant activity of the methanol extract of patikala (Etlingera elatior (Jack) RMSm) flowers had a weak antioxidant activity with the IC50 value of 101,84 mg/mL and the methanol extracts of patikala (Etlingera elatior (Jack) R.M.Sm) leaves had a strong antioxidant activity with IC50 value of 30,65 mg/mL. However, these antioxidant activities were lower than that of quercetin with IC50 value of 5.35 mg/mL.